The Antarium: A Reconstructed Visual Reality Device for Ant Navigation Research - Kócsi, Zoltán; Murray, Trevor; Dahmen, Hansjürgen; Narendra, Ajay; Zeil, Jochen (Frontiers in Behavioral Neuroscience, 2020)
We constructed a large projection device (the Antarium) with 20 000 UV-Blue-Green LEDs that allows us to present tethered ants with views of their natural foraging environment. The ants walk on an air-cushioned trackball, their movements are registered and can be fed back to the visual panorama. Views are generated in a 3D model of the ants’ environment, so that they experience the changing visual world in the same way as they do when foraging naturally. The Antarium is a biscribed pentakis dodecahedron with 55 facets of identical isosceles triangles. The length of the base of the triangles is 368 mm resulting in a device that is roughly 1m in diameter. Each triangle contains 361 blue/green LEDs and 9 UV LEDs. The 55 triangles of the Antarium have 19,855 Green & Blue pixels and 495 UV pixels, covering 360o azimuth and elevation from -50o below horizon to +90o above the horizon. The angular resolution is 1.5o for Green and Blue LEDs and 6.7o for UV LEDs, offering 65,536 intensity levels at a flicker frequency of more than 9,000 Hz and a framerate of 190 fps. In addition, the direction and degree of polarisation of the UV LEDs can be adjusted through polarisers mounted on the axles of rotary actuators. We build 3D models of the natural foraging environment of ants using purely camera-based methods. We reconstruct panoramic scenes at any point within these models, by projecting panoramic images onto 6 virtual cameras which capture a cube-map of images to be projected by the LEDs of the Antarium. The Antarium is a unique instrument to investigate visual navigation in ants. In open loop, it allows us to provide ants with familiar and unfamiliar views, with completely featureless visual scenes, or with scenes that are altered in spatial or spectral composition. In closed loop, we can study the behavior of ants that are virtually displaced within their natural foraging environment. In future, the Antarium can also be used to investigate the dynamics of navigational guidance and the neurophysiological basis of ant navigation in natural visual environments.